THE NATIONALIST DISCOURSES IN THE SFRY BEFORE ITS DISINTEGRATION (Heritage, 2023)
This paper presents the nationalist discourses in the SFRY before its disintegration and how ethnic nationalism was instrumentalized to achieve the political elites' goals. Based on the previous studies, it presents the basic features of nationalist discourses in the former Yugoslav republics before the collapse of the SFRY, the ways of their construction, dissemination, and popularization, the social actors who played a key role in it, the motives behind the rise of ethnic nationalism and the implications it had. The paper covers the period from the beginning of the 1980s to 1991 when Slovenia and Croatia declared independence and when the first armed conflicts began. Given that Slovenia, Croatia, and Serbia played a key role in the breakup of Yugoslavia, this paper presents nationalist discourses in only these three republics. Since the beginning of the 1980s, the rise of nationalism in SFRY was supported by numerous factors: the still prevalent feelings of national belonging among the people that weren’t fully suppressed; the Constitution adopted in 1974, that gave sufficient autonomy to each republic, leaving space for nationalism; Tito's death; fall of socialism; general social and economic crisis. Political structures of that time used nationalism to stay in power, alongside tradition, religion, mythologization of history, self-victimization, and demonization of the Other. The political instrumentalization of nationalism and tradition was prominent in Serbia and Croatia, but more aggressive in Serbia. In Slovenia more prevalent was a discourse on self-victimization and demonization of the Other, Serbia especially. Mythological discourse focuses on the safe and ‘better’ past, covering up the ugly present and blurring the uncertain future. Highlighting the external enemy, this discourse distracts attention from the internal ones, preventing any criticism of the government.
Keywords: the disintegration of SFRY; nationalism; the political instrumentalization of nationalism and tradition; the mythologization of history; self-victimization; the demonization of the Other